KNOWLEDGE OF THE POPULATION ATTENDED IN BASIC HEALTH UNITS IN THE SOUTHWEST REGION OF ANÁPOLIS-GO ABOUT SYPHILIS - Dias, Lorrayne Leite; Roberto, Giovanna Luiza Silva; Moraes, Letícia Karen de; Arruda, Jalsi Tacon; Moura, Léa Resende (CIPEEX, 2025)
Syphilis is a bacterial, systemic sexually transmitted infection (STI) caused by the etiological agent Treponema pallidum. There are three routes of transmission: sexual contact, mother-to-child during childbirth, or blood transfusion. Currently, there is no vaccine against syphilis, and infection does not confer protective immunity. Brazil is experiencing a syphilis epidemic, with the number of cases increasing every year. This study aims to analyze the knowledge of the population served by Basic Health Units (BHUs) in the Southwest region of Anápolis, GO, Brazil, about syphilis. It consists of an observational, cross-sectional, and descriptive study conducted in BHUs in the Southwest region of Anápolis, GO, Brazil, where a questionnaire was applied to assess the population’s knowledge about syphilis. This research obtained 39 eligible participants. Of these, the majority were female, aged between 41 and 50 years, brown-skinned, and married. Most participants identified the wrong etiological agent, but correctly identified the forms of transmission and prevention and the clinical manifestations of the disease. When scoring their knowledge, 58.9% classified themselves as having some knowledge (11-15 points). Finally, this study may contribute to the development of health promotion interventions in the city of Anápolis, GO, on this subject.